(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In this essay we will make a comparative analysis of Retábulo de Santa Joana Carolina, published in 1991, theatricalized by Maria Jose de Carvalho, in comparison with the original work of Osman Lins, that was published in 1966. The text is a theatricalization by Maria Jose de Carvalho, as it’s told in the edition of 1991. The new edition contains both the adapted version and the original work by Osman Lins. This edition is still composed by illustrations by Marianne Jolowicz, a preface by Julieta de Gody Ladeira, as well as a portic by Maria Jose de Carvalho. We will go through Lins’ paths of construction in his work Retábulo and the resources that Carvalho used to take it to theater.